Persepsi Mahasiswa Tentang Profesionalitas Dosen Jurusan Ushuluddin Dan Syariah STAIN Kediri Dan Korelasinya Dengan Keberhasilan Perkuliahan - Hadi, Noer (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2015)
This study focuses on the learning success and its reciprocal correlation with teacher professionalism according to the student perspective. The present study is necessary to conduct, since as one evidence of teacher professionalism, teacher certification, according to Peraturan Pemerintah Number 37 year 2009 Chapter 7, is valid as long as a teacher does their assignment as teachers, and is not evaluated regularly. Meanwhile, teacher evaluation, according to James H. Strongs, is considerably needed to improve teacher professionalism in order that teachers can provide the best quality learning experience to all their students. The data collection technique employed in the present study was questionnaire. The respondent was all students of the Departments of Ushuludin and Syari’ah, studying in semester III, V and VII who were having classes when the data were collected, with a total of 681 students. Pearson Product Moment was then employed to analyze the data, since the data of the two variables were interval and normally distributed. The present study oncludes that, firstly, 11 (1.62%) of the students assess that the ssionalism of their teachers is very bad, 39 (5.73%) bad, 200 (29.3%) fair, 192 (19%) ood, and 13 (1.91%) very good. Secondly, 13 (1.31%) of the students ought that the success of their learning was very bad, 44 (6.46%) bad, 192 28.19%) fair, 308 (45.23%) good, and 124 (28.21%) very good. Thirdly, eacher professionalism is positively correlated with the learning success; the ontribution of teacher professionalism for the learning success is 33.18%, hile the other 66.82% is affected by other variables.